The impact of GC bias on phylogenetic accuracy using targeted enrichment phylogenomic data - Bossert, Silas; Murray, Elizabeth A.; Blaimer, Bonnie B.; Danforth, Bryan N. (Molecular phylogenetics and evolution, 2017)
[Display omitted] •In-silico captured ultraconserved elements of bee genomes provide an ideal system to study incongruence.•A matrix of 810 loci supports the Euglossini as sister to the remaining corbiculate Apidae.•Coalescent-based methods reveal significant topological conflict among gene trees.•Binning the genomic loci based on GC content reveals heterogeneous support.•GC bias can be present in ultraconserved elements. The field of sequence based phylogenetic analyses is currently being transformed by novel hybrid-based targeted enrichment methods, such as the use of ultraconserved elements (UCEs). Rather than analyzing relationships among organisms using a small number of genes, these methods now allow us to evaluate relationships with many hundreds to thousands of individual gene loci. However, the inclusion of thousands of loci does not necessarily overcome the long-standing challenge of incongruence among phylogenetic trees derived from different genes or gene regions. One factor that impacts the level of incongruence in phylogenomic data sets is the level of GC bias. GC rich gene regions are prone to higher recombination rates than AT rich regions, driven by a process referred to as “GC biased gene conversion”. As a result, high GC content can be negatively associated with phylogenetic accuracy, but the extent to which this impacts incongruence among UCEs is currently unstudied. We investigated the impact of GC content on phylogeny reconstruction using in silico captured UCE data for the corbiculate bees (Hymenoptera: Apidae). The phylogeny of this group has been the subject of extensive study, and incongruence among gene trees is thought to be a source of phylogenetic error. We conducted coalescent- and concatenation-based analyses of 810 individual gene loci from all 13 currently available bee genomes, including 8 corbiculate taxa. Both coalescent- and concatenation-based methods converged on a single topology for the corbiculate tribes. In contrast to concatenation, the coalescent-based methods revealed significant topological conflict at nodes involving the orchid bees (Euglossini) and honeybees (Apini). Partitioning the loci by GC content reveals decreasing support for the inferred topology with increasing GC bias. Based on the results of this study, we report the first evidence that GC biased gene conversion may contribute to topological incongruence in studies based on ultraconserved elements.